Cuidador de idosos com doença de Alzheimer: efeitos de grupos psico-educacionais e suporte domiciliar individualizado - Faleiros, Danilo Augusto de Melo (Universidade Federal de São Carlos, 2009)
Dementia involves the loss of cognitive functions, interfering with the execution of even the most basic tasks of everyday life. Family eldercare providers are central figures in guaranteeing the wellbeing of their elderly relatives who develop dementia. However, when such a person becomes dependent on other family members, in addition to an increase in the caregiver s domestic chores, the behavior problems that arise can have a negative impact when caregivers are not well prepared for this situation, making the caregivers more susceptible to depression and contributing to the deterioration of their own physical and psychological wellbeing, making the caregiving context even more difficult. The objective of this study was to analyze the effects of psycho-educational support groups (PEG) for people caring for a relative with Alzheimer s disease (AD), associated with individual, home visits that were either training-oriented (Experimental Group EG) or listening-oriented (Control Group CG) in nature, with respect to the participants perceptions of burden, depressive symptoms and quality of life. The nine participants were randomly assigned to either the EG and CG. The EG participants received encouragement and assistance in operationalizing the concepts learned in the PEG, which addressed strategies for managing stress and depression and provided training in some of the social skills that are useful in establishing new routines (praise, constructive criticism, and asking for help). The CG received visits of the same duration, bus focused only on listening. The participants were interviewed about their situation, but did not receive individual assistance in operationalizing the strategies presented in the PEG. At the end of the first phase of the intervention, each group received the other type of home-based intervention. The data were analyzed using nonparametric tests (Mann-Whitney and Wilcoxon). The psycho-educational groups were effective in transmitting information, but did not reduce the caregivers perceptions of burden, reporting of depressive symptoms or change their quality of life ratings. After the caregivers received the training-oriented home visits (TV), their perceptions of burden significantly decreased and their quality of life ratings increased. The listeningbased visits had no significant effects on the caregivers. Six months later, an analysis of the follow-up measures indicate that improvements in perceptions of burden, frequency of depressive symptoms and quality of life scores were maintained by those who experienced the PEG coupled with TV. In conclusion, it is clear that professionals who offer orientation programs for family members caring for elderly relatives who have AD should further invest in evaluating the influence of home visits that focus on assisting these caregivers in adjusting their managerial and coping strategies, so as to increase our knowledge of how to blend group-based and individual psycho-educational supports in order to maximize the effects of such interventions.
Keywords: Educação especial; Cuidador familiar; Sobrecarga no cuidador; Grupos psicoeducativos; Assistência domiciliar; Atendimento psicológico; Doença de Alzheimer; Psycho-educational groups; Alzheimer s disease; Caregiver; Caregiving effects; In-home services; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL